PENGARUH PENGGUNAAN SHOPEE PAY LATER TERHADAP PERILAKU KONSUMTIF MAHASISWA DI KOTA MAKASSAR - Hasma Fitrayanti; Basri Basir MR; Wahyuni (ITB AAS Indonesia Surakarta, 2026)
This study examines the use of Shopee Pay Later in relation to students' consumptive behavior in Makassar City. The analysis results indicate that there is no significant influence of Shopee Pay Later usage on students' consumptive behavior, as shown by the simple linear regression test, with a negative regression coefficient of -0.028 and a significance value of 0.815 (>0.05). In the context of financial accounting, this finding suggests that access to digital credit does not necessarily increase consumption but is influenced by other factors such as debt management and cash flow planning. Furthermore, this study highlights the potential for financial distress due to the uncontrolled use of digital credit services. Therefore, understanding financial management and liability recording is essential to maintaining students' financial stability. Keywords: Consumptive Behavior, Financial Distress, Shopee Pay Later.